Custeio do fluxo de valor: um estudo empírico da metodologia de custeio da contabilidade enxuta (lean accounting) - Barros, Luis Fernando da Silva (2012)
This study aims to apply the value stream costing, the lean accounting costing methodology, pursuing identify its benefit and compare it with the traditional costing methodology. Also, the study sought to identify the information need for the value stream costing and how that information could be structured to enable the value stream costing. In order to answer those questions this study was based on a case study of an electrical manufacture products and solutions company. In Brazil, the lean accounting studies related are still in the beginning, mainly if taken into account the number of empirical research, which are very few. Based on that, this study has its relevance as it will serve as a basis for future studies, as well as in contributing to the expansion of knowledge about the concepts of lean accounting and its costing methodology: The value stream costing. Thus, the first question asked to direct this research is: What benefits can a company have using the costing value stream costing methodology? To answer the first question, it was necessary to apply a cost model based on the value stream costing and with that comes a second question which guided the research: What are the data and information required to enable the value stream costing? As a result of this study, were identified and assessed the benefits of value stream costing and identified the necessary information for the application of this costing methodology